Thyroid eye disease or Graves’ orbitopathy: What name to use, and why it matters - Wagner, Lilly H.; Bradley, Elizabeth A.; Tooley, Andrea A.; Ren, Yanhan; Rachmasari, Kharisa N.; Stan, Marius N. (Frontiers in Endocrinology, 2022)
There is currently no universally accepted name for inflammatory disease of the eye and orbit associated with thyroid autoimmune disease. Variability in terminology impedes the evaluation of scientific literature and clinical collaboration and can affect patients’ understanding of a disease process. The goals of this perspective article are 1. To compare the frequency of different terms used for eye disease associated with autoimmune thyroid disease in the scientific literature between 2000, 2010 and 2020 publications; 2. To investigate potential associations of terminology with author and journal specialty, and multidisciplinary vs. mono-disciplinary author teams; 3. To determine preferential terms used by professional societies; and 4. To propose standardized terminology based on our data analysis. The methods for this study included review of all English language articles listed in PubMed, with publication dates in the years 2000, 2010 and 2020, that included one of 6 terms currently used to describe eye disease associated with autoimmune thyroid disease. Characteristics pertaining to authors, journals, and article type were recorded. Results showed that the most used term in the 2000 literature was Graves’ Ophthalmopathy (61%). In the 2010 literature, Graves’ Orbitopathy (31%) became most common, followed by Graves’ Ophthalmopathy (30%). Between 2010 and 2020, thyroid eye disease (37%) became the most common term, followed by Graves’ Orbitopathy (35%). This perspective article proposes “thyroid eye disease” (TED) as the preferred name for this entity and discusses supporting terminology patterns and trends over time in scientific literature and in professional societies.